Using Collaborative Action Research to Address Bullying and Violence in a Colombian High School EFLClassroom - Ortega, Yecid (Íkala, Revista de Lenguaje y Cultura, 2020)
This paper describes how a collaborative action research project implemented in an underprivileged high school in Bogotá helped an English teacher and her students discuss issues of social justice with a special focus on bullying. It also discusses how the English teacher used her class to connect global and local issues to sensitize students to their own social inequalities. To do this, the teacher used social justice, critical peace education, and globalization as a framework that guided her research and practices. The students, the teacher, and I, as a researcher, collaborated to cocreate lessons whereby students were conscientized about normalized aggression in the school. The findings of this research suggest the following (a) students became more sensitive to and aware of the violent culture that existed in the school, (b) the activities empowered them to become advocates for social change, and (c) the actions taken translated into the community becoming central as praxis. I conclude that the English classroom has the capacity for social transformation as it allows for alternative pedagogical approaches targetting the students’ needs.